2021
DOI: 10.24818/beman/2021.11.4-04
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure: Evidence From Indonesian Palm Oil Companies

Abstract: This study to find out the determinants of capital structure in the palm oil industry in Indonesia. The variables are commodity prices, total assets, tangible assets, profitability, asset turnover, liquidity, inventory turnover, interest rates, and capital structure as independent variables. The data processing uses SPSS version 25 and performs classical assumption test, coefficient of determination test, and multiple regression analysis. The object of this study is oil palm plantation companies listed in Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…LQTY negatively and significantly affects capital structure (Nurwulandari, 2021). The study's findings demonstrated that PFTY, LQTY, and AS had negative and notable effects on capital structure (Dewi et al, 2021). Doan (2019) reported that foreign ownership, AS, PFTY, and LQTY all have unfavorable relationships with capital structure.…”
Section: Liquidity and Capital Structurementioning
confidence: 85%
See 1 more Smart Citation
“…LQTY negatively and significantly affects capital structure (Nurwulandari, 2021). The study's findings demonstrated that PFTY, LQTY, and AS had negative and notable effects on capital structure (Dewi et al, 2021). Doan (2019) reported that foreign ownership, AS, PFTY, and LQTY all have unfavorable relationships with capital structure.…”
Section: Liquidity and Capital Structurementioning
confidence: 85%
“…PFTY has a detrimental impact on FL (Sutomo et al, 2020). Return on assets, an indicator of PFTY, is inversely connected (Dewi et al, 2021). Sayılgan et al (2006) concluded that, for Turkish enterprises' capital structure decisions, PFTY is negatively connected to FL.…”
Section: Profitability Of the Firm And Capital Structurementioning
confidence: 99%
“…The influence of macroeconomic indicators, such as the Consumer Price Index, Industrial Production Index, Money Supply, Stock Market Index, Exchange Rate, Consumer Confidence Index, and Composite Economic Leading Indicator, on the future volatility of commodities (Mo, et al, 2018). Additionally, commodity prices are frequently suspected as a reference for businesses involved with these commodities (Dewi, et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%